ASURANSI SYARIAH SEBAGAI ALTERNATIF INVESTASI - Humaeroh Humaeroh (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
Insurance takes the leading sectors in modern economic world. Most economic theorists argue that the core of insurance is formed on eliminating uncertain risk of loss for a group of people facing similar problems, and paying premiums on a general fund that is a compensation of losses caused by any member and all risks do not get the same costs in insurance. The Uncertaintychance and speculation caused a reaction among religious scholars and Muslim intellectuals. The beginning of Sharia insurance in Indonesia is a phenomenon that should be raised, in view of theinsurance development in the country isgenerally still under the progress achieved in other countries, especially the ratio of Muslims populationin Indonesia with the number of policyholders are still less balanced. Awareness of the importance of insurance for the people of Indonesia is not evenly distributed. They still think that saving in the bank is much more secure than being an insurance participant.Lack of socialization about insurance by the state and insurance institutions is one of the factors of infamous insurance that can provide life protection, property protection, health protection, protection of education, protection of old age and so forth..